Impact of farmer professional cooperative on safety production behavior in terms of quality and safety of agricultural products - Teng, Yun; Chen, Xinlin; Zhang, Mei (Frontiers in Public Health, 2022)
“How to realize farmers to actively produce quality and safety agricultural products” has become a common problem faced by researchers and practitioners. Based on the Triadic Reciprocal Determinism theory and Behavior-motivation theory, the study tries to answer this question from the perspective of standardized farmer professional cooperatives in China, and then solve relevant international problems. The empirical results of 767 sample data using SPSS-AMOS methods show that the restraint factors of standardized farmer professional cooperative have positive effects on safety negative behavior and negative impact on safety positive behavior, and the motivation factors of standardized farmer professional cooperatives have positive effects on safety positive behavior. The restraint factors of farmer professional cooperatives have a positive impact on safety controlled motivation and negative impact on safety autonomous motivation, and the motivation factors of farmer professional cooperatives positively affect the safety autonomous motivation. The safety controlled motivation positively affects safety negative behavior and safety autonomous motivation negatively affects safety negative behavior and positively impacts on safety positive behavior. The above findings theoretically make a useful supplement to the study of farmers' safety production behavior, and have guiding significance to the construction of standardized farmer professional cooperatives in the world.